School strategies on improving students’ physical activity engagement during COVID-19 pandemic period: a thematic review - Piores, Victor Fello; Omar Dev, Roxana Dev; Muhamad, Mohd Mokhtar; Puad Mohd Kari, Dharatun Nissa (OVS LLC, 2024)
Study purpose. Physical inactivity among school students was an existing health issue over the past decade. This became more alarming when the world was hit by the COVID-19 pandemic. Movement restriction that results temporary school closure significantly affect students’ physical activity participation. Therefore, strategies and practices to improve active play engagement as well as to counteract its negative health-related effects on students were widely implemented by teachers and administrators in school upon its re-opening. Numerous articles have been published on the effectiveness of school-based interventions during the COVID-19 pandemic, but there is still a lack of a review paper that deals with the identification of patterns and trends about school practices in this area. Hence, this paper intends to generate impressions and identify concepts within the published articles during 2021 to 2023. Materials and methods. Selected articles for this study were collected from the following databases: SCOPUS, Sage, ProQuest, Academic Search complete, Science Direct. Computer-assisted qualitative data analysis (ATLAS ti. 23) guided the comprehensiveness of this review. Study findings were generated and presented through quantitative and qualitative lenses. Results. Four central themes were identified: 1) Alternative Physical Education – modifying traditional physical education subject; 2) Physical literacy focus – approach anchored to multi-dimensional foundation in physical activity engagement 3) Web-based intervention – virtual and cyberspace approach and 4) Needs-based intervention – focusing on integration of participants’ attributes and specifically designed program. Conclusions. The structure of strategies conducted by schools were greatly affected by the current community health status. Findings of this study will serve as a reference for designing future intervention approach to address the sedentary lifestyles of young populations associated to specific community health and other related issues.